Requirements for a Basic Student Course in Robotics and Human–Robot Interaction—A User-Centered Approach - Marie Güntert; Jonas Birkle; Verena Wagner-Hartl (Education Sciences)
Due to an increasing number of robots in the working world, the interaction between humans and robots will become more and more frequent. Hence, the research field of human–robot collaboration is becoming progressively relevant and should therefore be included in students’ education as early as possible. This paper deals with the requirements of a basic course for university students of interdisciplinary studies like Engineering Psychology or Human Factors. The goal of the course is to provide an adequate training for the students in order to gain a technical basis to design human–robot collaboration in a user-centered way in their future working life. Following a user-centered approach a narrative description and analysis of the context of use with contextual interviews were conducted. Overall, 12 subjects of the identified user groups (1) students studying Engineering Psychology, (2) students with knowledge in robotics and (3) graduates of the Engineering Psychology program participated in the contextual interviews. With these interviews, 47 user and stakeholder needs and 39 user requirements were derived. Based on the results, relevant content of a basic student course was defined, structured and prioritized. The requirements and demands are summarized in a recommendation for action and further steps are presented.